A picture is worth a thousand words: applying natural language processing tools for creating a quantum materials database map. (December 2019) - Venugopal, Vineeth; Broderick, Scott R.; Rajan, Krishna
Abstract: Abstract : This paper demonstrates the application of Natural Language Processing (NLP) tools to explore large libraries of documents and to correlate heuristic associations between text descriptions in figure captions with interpretations of images and figures. The use of visualization tools based on NLP methods permits one to quickly assess the extent of the research described in the literature related to a specific topic. The authors demonstrate how the use of NLP methods on only the figure captions without having to navigate the entire text of a document can provide an accelerated assessment of the literature in a given domain.